Mothers and sons;centering mother knowledge. (DEMETER Press, 2016)
Mothers and Sons: Centering Mother Knowledge makes a case for the need to de-gender the framing and study of parental legacy. The actualization of an entire collection on this dyad foregrounding motherhood without particularizing the absence of fatherhood is in itself revolutionary. This assemblage of analytical, narrative and creative renderings offers cross-disciplinary conceptualizations of maternal experiences across difference and mothering sons at intersections. The authors' mother knowledge, or that of their subjects, delivers new insights into the appellations mother, son, motherhood a.